A molecular pathological study of four cases of ciliated muconodular papillary tumors of the lung. Issue 6 (6th April 2018) - Kataoka, Toshiaki; Okudela, Koji; Matsumura, Mai; Mitsui, Hideaki; Suzuki, Takehisa; Koike, Chihiro; Sawazumi, Tomoe; Umeda, Shigeaki; Tateishi, Yoko; Yamanaka, Shoji; Ishikawa, Yoshihiro; Arai, Hiromasa; et al.
Abstract : Ciliated muconodular papillary tumors (CMPTs) are a recently categorized benign or low‐grade malignant neoplasm that develops in the peripheral lung. Only about 40 cases have been reported to date, and the clinicopathological characteristics have yet to be defined in detail. Here, we present four cases of CMPTs with a focus on their immunohistochemical profiles and driver gene mutations. These tumors were a papillary proliferation of a mixture of ciliated, mucous, and basal cells located in the peripheral lung. Ciliated, mucous and basal cells were positive for TTF‐1 when using the clone SPT24, but negative for HNF‐4α. Basal cells were positive for p40. Mucous cells in some tumors were positive for MUC5AC and MUC6. The Ki‐67 index was less than 5%, and strong expression of p53 was not detected. Three of the four tumors had a BRAF (V600E) driver mutation, an EGFR (del E746‐T751/S752V) driver mutation, or driver mutations in both EGFR (E709G) and KRAS (G12V). These mutation types are rare for any histological type of lung cancer. The present results confirmed that CMPT is a neoplasm with immunohistochemical features and driver gene mutations that are distinct from those of common lung tumors.